KEPUASAN KERJA GURU DITINJAU DARI KEPEMIMPINAN TRANSFORMASIONAL KEPALA MADRASAH DAN BUDAYA ORGANISASI - Muhammad Sulaeman; M. Entang; Hari Muharam (Universitas Pakuan, 2018)
The objective of this research is to outline the correlation of principal transformational leadhership and organization culture with teacher work job satisfaction. This research was conducted in Islamic junior school Kadudampit district by applying survey analysis method and the data were collected from the given quessionnaires. 153 of population and 111 of samples were taken by using proportional random sampling. The research findings reveals that: 1) there is a principals positive correlation between transformational ledhership with teacher job satisfacttion, 2) there is principals positive correlation between organization culture with teacher job satisfaction., 3) there is principals positive correlation between transformational leadhership and organization culture with teacher work job satisfaction. The findings of this research shows that teacher job satisfaction can be achieved through improvement of transformational ledhership and organization culture.Keywords : Transformational leadership, Organizational Culture, teacher Job Satisfaction.